Economic well-being of selected administrative staff of an urban public university: A qualitative study - Mohamed Harith, Nor Hafizah; Md. Noon, Hazizan (AMER ABRA by e-International Publishing House, Ltd, 2016)
The trend of urbanization in Malaysia is increasing and presently sixty-seven percent (67%) of the Malaysia’s population are living in the urban regions. Therefore, the concern over the quality of life of the urban residents becomes more crucial in the Malaysian government’s policy. It can be predicted that the urban population will face greater obstacles in availing the opportunities and coping with the challenges of living in the cities. In this regards, the economic well-being of the urban population is the central aspect affecting their subjective well-being (SWB). Hence, this research aims to explore how the economic well-being affects the subjective well-being (SWB) among the selected respondents who live in the major cities in the Klang Valley, Malaysia. Adopting the Allard's dimensions of welfare, this study explores the subjective meaning of life satisfaction among the administrative personnel of an urban public university, namely Universiti Teknologi MARA (UiTM). Sixteen key informants from four different categories of administrative staff of the University’s main campus in Shah Alam, Selangor were engaged in the researchers’ in-depth interviews. The main findings of this research have shown that the responses were centred on the coping ability adopted by the UiTM administrative staff to survive life in the urban areas.